2020
DOI: 10.1080/23738871.2020.1722191
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation in the DNS resolver market – how much, how fast, how dangerous?

Abstract: Almost all online services use a domain name resolution function to translate names typed by the user into numbers that computers understand. This basic, recursive function, performed in milliseconds and invisible to the user, was integrated from the beginning into the operation of Internet Service Providers (ISPs). This started to change with the advent of new playerssuch as Google, Cloudflare, Oracleoperating public resolvers and rendering the market more dynamic in the last decade. As more technologies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…In particular, Mueller (2010) has stressed the need to examine internet engineering networks more systematically, and general literature has highlighted the diversity of conceivable network outcomes (Kim, 2019). Broadening the debate is also important since related literature shows that, besides fragmentation, the internet as well as large networks in general can foster outcomes such as concentration around selected actors (Barabási and Albert, 1999; Journal of Cyber Policy , 2020; Radu and Hausding, 2020). Similar dynamics might be at work in engineering networks.…”
Section: Two Contributions To the Internet Fragmentation Debatementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Mueller (2010) has stressed the need to examine internet engineering networks more systematically, and general literature has highlighted the diversity of conceivable network outcomes (Kim, 2019). Broadening the debate is also important since related literature shows that, besides fragmentation, the internet as well as large networks in general can foster outcomes such as concentration around selected actors (Barabási and Albert, 1999; Journal of Cyber Policy , 2020; Radu and Hausding, 2020). Similar dynamics might be at work in engineering networks.…”
Section: Two Contributions To the Internet Fragmentation Debatementioning
confidence: 99%
“…Finally, organizational concentration has received less attention in studies of transnational engineering networks but has played a prominent role in the wider literature on the digital economy, which suggests that the scale and logic of internet‐based activity fosters high concentration of market shares and authority in few actors ( Journal of Cyber Policy , 2020). Recently studies have suggested that concentration dynamics might influence internet governance in general and engineering networks in standard‐setting (Gahnberg, 2019; Internet Society, 2019; Journal of Cyber Policy , 2020; Radu and Hausding, 2020; Simcoe, 2012). It is uncontested that companies are the main actors in internet standard‐setting.…”
Section: Political Structuring and Organizational Concentrationmentioning
confidence: 99%
“…The TXT answer contained the IP addresses of external servers for downloading another payload to complete the C2 access. Both approaches exploit the fact that Google DNS is the most popular DNS resolver [67];thus it is probably accessible.…”
Section: Taxonomy Of Doh Abuse: Tools and Malwarementioning
confidence: 99%
“…Zembruzki et al [30] found that up to 12,000 name servers used by websites in the Alexa top 1 million shared the same third-party infrastructure. As for public resolvers, Radu et al [27] found that the popularity of Google's public DNS resolver has increased tremendously over time, serving as the default resovler for over 35% of studied clients. The popularity of public DNS resolvers might be explained by their lower response times in comparison to that of local resolvers, despite the advantage being dependent on client location [13].…”
Section: The Domain Name System (Dns)mentioning
confidence: 99%